Intravascular histiocytosis: case report of a rare disease probably associated with silicone breast implant, - Yasmin Gama Abuawad; Ticiana de Andrade Castelo Branco Diniz; Priscila Kakizaki; Neusa Yuriko Sakai Valente (Sociedade Brasileira de Dermatologia, 2020)
Abstract Intravascular histiocytosis is a rare condition characterized by the aggregate of histiocytes within dilated dermal vessels. The diagnosis is mainly histophatological and immunohistochemical. We describe a case of a 55 year-old female patient presenting erythematous/purple patches on the breasts, back and limbs. She previously presented ductal carcinoma in the right breast in 2006 which was treated with mastectomy and proceeded to silicone breast implant in 2009. Clinical hypothesis was telangiectatic metastatic carcinoma. Histopathology showed vascular ectasia, thrombosis and recanalization of upper dermis small vessels. On immunohistochemistry, intravascular cells were CD 68+ and negative for estrogen and progesterone receptors, CK7, EMA and AE1/AE3 and endothelial cells were CD64+, leading to the diagnosis of intravascular histiocytosis.